LA PERFORMANCE MORPHOSYNTAXIQUE DANS LES TÂCHES DE REFORMULATION ÉCRITE. CAS D’ÉTUDIANTS DÉBUTANTS DE FLE - Karpińska-Szaj, Katarzyna; Wojciechowska, Bernadeta (Neofilolog, 2019)
In this article the relation between the discourse production dynamic and the linguistic competence development is discussed. This problem is considered with regard to two types of language activities based on reformulation tasks: 1) written reconstruction of a story heard, 2) written production of the end of the story. The analysis of experimental data shows that in the second case the approach to the discourse is more complete which positively influences application of complex morphosyntactic structures in students production.